2017
DOI: 10.1021/acsami.7b11257
|View full text |Cite
|
Sign up to set email alerts
|

TiO2 Nanorod Arrays with Mesoscopic Micro–Nano Interfaces for in Situ Regulation of Cell Morphology and Nucleus Deformation

Abstract: Cell morphology and nucleus deformation are important when circulating tumor cells break away from the primary tumor and migrate to a distant organ. Cells are sensitive to the microenvironment and respond to the cell-material interfaces. We fabricated TiO nanorod arrays with mesoscopic micro-nano interfaces through a two-step hydrothermal reaction method to induce severe changes in cell morphology and nucleus deformation. The average size of the microscale voids was increased from 5.1 to 10.5 μm when the hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…Importantly, these micro‐nano‐sized interfaces were fabricated by one‐step electrochemical deposition, which was easier than the two‐step hydrothermal reaction method. [ 23 ] The cross section of CaP‐1 and CaP‐2 were shown in Figure 2c,f. Results indicated that the thickness of CaP films was increased from 3 to 12 µm when the electrochemical time was increased from 2.5 to 10 min.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, these micro‐nano‐sized interfaces were fabricated by one‐step electrochemical deposition, which was easier than the two‐step hydrothermal reaction method. [ 23 ] The cross section of CaP‐1 and CaP‐2 were shown in Figure 2c,f. Results indicated that the thickness of CaP films was increased from 3 to 12 µm when the electrochemical time was increased from 2.5 to 10 min.…”
Section: Resultsmentioning
confidence: 99%
“…These results were similar to the cancer cells morphology on the micro‐nano TiO 2 bio‐interfaces. [ 23 ] On the micro‐nano interfaces, more pseudopodia can be found on the structural skeleton (Figure 3f), that is, the cancer cells needed more pseudopodia to capture the CaP nanosheets to support the HepG2 cell weight. The analogous interaction between HepG2 cells and CaP substrates can offer more chance for target cells, which induced higher HepG2 cells capture efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…The effects of the TiO 2 biointerface on the mechanics-induced cell membrane deformation has been thoroughly investigated by Liu et al [ 88 ] They showed that TiO 2 NRs, produced by a two-step hydrothermal approach, modified the cell morphology and the nuclear shape of MCF-7 cells. In particular, the etching time during the hydrothermal synthesis tuned the size of the voids between TiO 2 NRs.…”
Section: Tio 2 -Based 1d Materialsmentioning
confidence: 99%
“…The higher the etching time, the larger the spaces between the NRs. The resulting voids induced a reversible mechanical deformation of the nuclei, regulating the pressure exerted by actin under the nucleus [ 88 ]. Similarly, Peng et al [ 89 ] observed an increased C3H10T1/2 cell adhesion along with reduced adhesion and colonization of Staphylococcus epidermidis (i.e., a pathogen associated with orthopaedic infections) in comparison with Ti surfaces.…”
Section: Tio 2 -Based 1d Materialsmentioning
confidence: 99%
“…UV-photodetector, resistive switching memory devices, and capacitors based on the TiO 2 nanorod array have been developed. The TiO 2 nanorod array has been utilized for application as a platform for photoelectrochemical bioanalysis and capture of tumor cells. …”
Section: Introductionmentioning
confidence: 99%